Congenital double bile duct presenting as recurrent cholangitis in a child - K.D. Chakravarty; Jaya Agarwal; A.C. Praveen Kumar (Elsevier, 2015)
Double common bile duct (DCBD) is a rare congenital anomaly. Most of these bile duct anomalies are associated with bile duct stones, anomalous pancreaticobiliary junction (APBJ), pancreatitis and bile duct or gastric cancers. Early detection and treatment is important to avoid long term complications. Surgical resection of the anomalous bile duct and reconstruction of the biliary enteric anastomosis is the treatment of choice. We report a rare case of DCBD anomaly in a girl, who presented with recurrent cholangitis. She had type Va DCBD anomaly. She underwent successful resection of the bile duct and reconstruction of the biliary enteric anastomosis. Preoperative imaging and diagnosis of the congenital biliary anomaly is very important to avoid intraoperative bile duct injury. Review of the literature shows very few cases of type Va DCBD, presenting with either bile duct stones or APBJ.